Musical Education in Kazan in 1917-1960: Periodization Problem - Nuriyeva, Liliya Faritovna; Martynov, Dmitry Evgenyevich; Martynova, Yulia Aleksandrovna (Journal of History Culture and Art Research, 2017)
This article is devoted to justification of a periodization in music history education in Kazan and TACCP from revolutionary events of 1917 to foundation of high special music school at the Kazan State Conservatory in 1960. The research implements historical & genetic and historical & comparative methods. Justification of specifics of historical and cultural processes in the region during the declared period and about applicability of a three-part periodization, the bases for which will be cultures of the decision of the political and party management, external for the sphere, is presented. Characteristic of Kazan was the fact that till 1960 the musical school was the only educational institution in TASSR providing secondary vocational music education. Conclusions are drawn that formation of new system of musical education began at the beginning of the 20th century, and local features were considered fully. The policy for the non-Russian population pursued by the Soviet power promoted further development of music education. The conducted research also showed that in Kazan synthesis of capital cultural tradition and regional features was carried out. Materials of article can be of interest to researchers of the USSR during the specified period, experts in history and culture of the Volga region people and history of music education in Eastern Europe.